A Cross-Sectional Comparative Study of the Performance of the Widal Test and the Typhidot Immunoassay for Typhoid Fever Diagnosis in the West Region of Cameroon - Karimo Ousenu; Innocent Mbulli Ali; Leonard Fonkeng Sama; Marcel Nsangou Ndam; Thibau Florant Tchouangueu; Christopher Bonglavnyuy Tume (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The diagnosis of typhoid fever based on the Widal slide agglutination test remains a major hurdle in developing countries due to varied perceptions of the value of the Widal test in determining clinical decision-making. We undertook a study to evaluate the diagnostic performance of the Widal test and the Typhidot immunoassay in patients suspected of having typhoid fever in the Menoua division, West Region of Cameroon. Methods. Blood and stool samples were collected from 558 consenting febrile patients on the basis of suspicion of typhoid fever. These patients attended three district health services of the Menoua division between April 2018 and September 2019. These patients had clinical symptoms suggestive of typhoid fever as determined by their consultant. Serum was used for the Widal slide agglutination test and for the Typhidot rapid immunoassay test based on manufacturer’s guidelines. A composite reference of fever plus positive coproculture for Salmonella typhi and Salmonella paratyphi was used as the reference. The sensitivity, specificity, and predictive values of the positive and negative tests were calculated as well as Cohen’s kappa for agreement between the two tests. Results. Of 558 patients, 12.90% tested positive for the reference method, 57.17% tested positive for the Widal slide agglutination test, while 15.59% were positive for Typhidot-IgM. The overall sensitivity, specificity, and predictive values of the positive and negative tests were 80.56%, 94.03%, 66.6%, and 97.03% for Typhidot-IgM and 94.44%, 48.35%, 21.32%, and 98.33% for the Widal slide agglutination test, respectively. Cohen’s kappa estimates were 0.1660 (0.121–0.211) and 0.386 (0.312–0.460) for the Widal test and Typhidot immunoassay for 53.6% and 76.16% agreements of all observations, respectively. Conclusion. The Widal test was found to have a lower predictive value for the diagnosis of typhoid fever in our setting. However, the Typhidot test, although better, was not ideal. Diagnosis of typhoid fever should therefore rely on adequate clinical suspicion and a positive Typhidot test to improve the clinical management of typhoid fever in our setting.